FISIBILITAS PILKADA SERENTAK TAHAP II KOTA PEKANBARU PASCA PERMENDAGRI NO 18 TAHUN 2015 - yandra, alexsander (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2017)
Feasibility Phase II simultaneous elections in the city of Pekanbaru post-Regulation No. 18 in 2015 affect the population administration and the right to vote of citizens, could be implicated cause some residents do not get a voter card. The Regulation boundary change Pekanbaru and Kampar namely RW 15,16 and 18 villages of three districts of the hill highway intersection that previously pekanbaru region into an area of Kampar. Thus, the Election Commission Pekanbaru as election organizers make an effort assessment mapping and data collection forms of suffrage of citizens in the disputed area in order to participate in the elections. Using descriptive qualitative method with theoretical concept of political interest in the election and Elections To Local as well as data analysis through interpretation of ethics and EMIC is further elaborated in the study of electoral governance in accordance with the discussion of the study. The results of this study demonstrate the efforts made by the Election Commission of Pekanbaru in data collection and mapping of suffrage of citizens in the border area of Pekanbaru and Kampar walk is not optimal for a long period of time but has shown improvement on the sustainability of suffrage in the interests of the election. Furthermore, citizens residence status does not match the expectations of citizens citizens in the response resulted in three RW at the intersection of three villages regarding the status of permanent voters list (DPT) on the elections, simultaneous phase II have a tendency not to vote.